(untitled) (JOURNAL OF ADVANCES IN CHEMISTRY, 2015)
Spectroscopic (IR,Â 1H-NMR, UV-visible, mass and ESR spectra) and structural studies of the ligand (1E, N’Z, N’Z)-N’, N’-bis (2-hydroxybenzylidene)-2-(naphthalen-1-yloxy) acetohydrazonohydrazide (H2L) and its metal complexes are reported. The magnetic properties and thermal analyses (DTA and TGA) were also carried out. The IR spectra of the prepared complexes suggested that, the ligand adopted either a bidentate or a tetradentate fashion, bonding to the metal ion through the azomethine nitrogens and the two phenolic oxygen atoms (ONNO). Electronic spectra and magnetic susceptibility measurements revealed an octahedral geometry for all complexes except sliver(I) complex (6), copper(II) complex (7) and cobalt(II) complex (11). The elemental analyses and mass spectral data have justified the ML, ML2Â and M3L composition of the complexes. The ESR spectra of copper(II) complexes (5), (7), (12) and (16), showed an axial type (dx2-y2) ground state with a covalent bond character and also support the suggested structures of complexes. The antimicrobial activity as well as the cytotoxicity of the ligand and its metal complexes were investigated and discussed.